Examining the role of urban form In shaping people’s accessibility to opportunities: An exploratory spatial data analysis - Scott, Darren; Horner, Mark (Journal of Transport and Land Use, 2008)
This study employs a comprehensive suite of accessibility indices to investigate whether American cities are designed in such a way that the locations of goods, services, and other opportunities favor certain socio-economic groups over others. In so doing, the study’s findings contribute to pressing policy issues such as social exclusion. Seven counties of the Louisville, KY-IN MSA serve as the study area for the investigation. Data are derived from three sources: a geocoded travel diary survey that was conducted in the study area in 2000, a geocoded database of all urban opportunities in the study area, and a database containing shortest path travel times between the locations of households and urban opportunities. Accessibility indices (i.e., gravity, cumulative opportunity, and proximity) are computed for households found in the trip diary survey. Furthermore, these indices are defined for 34 types of opportunities: four aggregate types (i.e., retail, service, leisure, and religious) and 30 disaggregate types representing the 10 most popular destinations for trips for each of the first three aggregate types. Non-parametric Wilcoxon rank sum tests are used to compare the accessibilities of five socio-economic groups (i.e., individuals residing in rural communities, individuals residing in single-person and single-parent households, individuals residing in low-income households, women, and the elderly) to their counterparts. Except for individuals residing in rural areas, our findings indicate that groups, which conventional wisdom would suggest are at risk of social exclusion, are not disadvantaged in terms of accessibility.